Kontribusi Limbah Kayu Daratan terhadap Sampah Laut di Pesisir Selatan Bali: Tinjauan Antropogenik dan Strategi Adaptasi Berbasis Ekosistem - Suryawan, I Wayan Koko (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The recurring accumulation of marine debris along the southern coast of Bali, particularly wood fragments and plastic waste, reflects the complex interaction between land-based human activities, climate change, and coastal oceanographic dynamics. This study aims to examine the potential contribution of terrestrial wood waste to marine debris in major tourist areas such as Kuta and Kedonganan beaches. The research applies a combined method of direct field observation during the west monsoon season and a comprehensive literature review, including secondary data on waste composition, ocean currents, and terrestrial waste management systems. Observations indicate that Kuta Beach is predominantly affected by wood debris such as branches and tree trunks while lighter plastic packaging is more common in areas like Kedonganan, suggesting that current strength influences the distribution of waste types. Analysis of household waste composition in several Bali districts reveals that wood and branch waste form a significant portion, particularly in Jembrana, Bangli, and Buleleng, supporting the hypothesis that much of the marine wood debris originates from upstream land-based sources via river systems. Intensified rainfall and riparian degradation—driven by land-use change and climate variability accelerate the transport of organic waste to the sea. This study recommends integrated ecosystem-based adaptation strategies, including lignolytic microbial decomposition, the installation of floating booms at river mouths, and the conversion of wood waste into circular economy products such as biochar through pyrolysis and wood-plastic composites.